Therapeutic advances in small cell undifferentiated carcinoma - Tomalino, Dante (Cirugía del Uruguay, 1982)
A considerable advacement in the treatment of small cell carcinoma of the lung has been recorded in the Jast 12 years. The greatest benefits come from the use of active chemoterapic agents applied in differents combinations necesary to obtain the complete remission for longs periods. The treatment in Protected Environment Prophylactic Antibiotic Units and methods for haematologic stimulation, hs allowed the app!ication of more agressive dosages and encouraging results. The radiant therapy and others resources adjuvants to chemotherapy allow the prediction of a better future for these patients. The survival over 2.4 years has become very frequent and with possibilities of cure.